2009
DOI: 10.1002/mrc.2438
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation on multinuclear NMR chemical shifts of some tris(trifluoromethyl)boron complexes

Abstract: Tris(trifluoromethyl)boron complexes have unusual properties and may find applications in many fields of chemistry, biology, and physics. To gain insight into their NMR properties, the isotropic 11B, 13C, and 19F NMR chemical shifts of a series of tris(trifluoromethyl)boron complexes were systematically studied using the gauge-included atomic orbitals (GIAO) method at the levels of B3LYP/6-31 + G(d,p)//B3LYP/6-31G* and B3LYP/6-311 + G(d,p)//B3LYP/6-311 + G(d,p). Solvent effects were taken into account by polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…An examination of the correlation between experimental and calculated spans (Figure ) suggested a potential relationship between ϕ CCBO and both the experimental and calculated Ω values. Previous work by Zhang et al reported a dependence of the computed energy of boronic acids on this dihedral angle . A plot of the value of Ω as a function of the calculated value of ϕ CCBO for each compound reveals no clear and direct correlation, which is not surprising, as there are several variables changing simultaneously.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…An examination of the correlation between experimental and calculated spans (Figure ) suggested a potential relationship between ϕ CCBO and both the experimental and calculated Ω values. Previous work by Zhang et al reported a dependence of the computed energy of boronic acids on this dihedral angle . A plot of the value of Ω as a function of the calculated value of ϕ CCBO for each compound reveals no clear and direct correlation, which is not surprising, as there are several variables changing simultaneously.…”
Section: Resultsmentioning
confidence: 82%
“…Previous work by Zhang et al reported a dependence of the computed energy of boronic acids on this dihedral angle. 54 A plot of the value of Ω as a function of the calculated value of φ CCBO for each compound reveals no clear and direct correlation, which is not surprising, as there are several variables changing simultaneously. For example, boronic acids have hydrogen bonding interactions taking place whereas the esters do not; the aromatic substituents are different on the various compounds, and the dihedral angle changes primarily due to sterics.…”
Section: Resultsmentioning
confidence: 94%
“…The calculated 19 F and 11 B chemical shieldings of (CF 3 ) 3 BCO are greatly dependent on the optimised structures, while the influence of structural parameters on the calculated 13 C chemical shieldings is minor. 168 Novel fluorinated boroxines, tris(2,6-difluorophenyl)boroxin (DF), tris(2,4,6-trifluorophenyl)boroxin (TF) and tris(pentafluorophenyl)boroxin (PF), were investigated for potential applications in lithium-ion batteries through fluoride anion binding, ab initio calculations and ionic cond. measurements.…”
Section: Barium ( 137 Ba) (I = 3/2) the Local Ba Environment In B-bamentioning
confidence: 99%